Förstärkning av förspänd bro med kompositmaterial - Sjöblom, Erik (2013)
Henningsvär is an island to the east of Lofoten, in northern part of Norway. The traffic to the island is increasing, especially during summer. Since the bridge to the island only has room for traffic in one direction at the time, the transport department in Norway wants to broaden the bridge to make room for two traffic lines. They want to investigate the possibility to strengthening the supporting structure with composite material to manage the increasing loads. This thesis will investigate how the composite material will work as reinforcing material to the supporting structure. The structure is formed as a concrete box girder with both normal and pretension reinforcement. The aim is to present strengthening methods for both shear and bending moment. To gain knowledge and understanding about the problem a research is made about prestressed concrete, composite material and strengthening methods. The loads from two traffic lines are used to get the new forces in the bridge. The new forces are then compared with the old capacity in both shear and bending moment to see where and how much strengthening the bridge needs to carry the new loads. Spännd To strengthening the bridge the use of carbon-fiber plates seems to be the best method. With this method all sections but one was able to carry the load in bending moment. In this study carbon-fiber sheets had to be used for shear force to gain required strengthening, but that is a very expensive method for this bridge. Because of conservative assumptions and boundaries the method with carbon-fiber plates seems to be the best strengthening solution for the bridge, in both shear and bending moment. Validerat; 20130319 (global_studentproject_submitter)